Advanced Health Control Consultation Application at Clinic B White C Based on Android - Iskandar, Akbar; Aman, Andryanto; Dayun Miyanti; Muhammad Akram Hamzah; Tatik Maslihatin (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
Health information is a vital aspect of daily life, typically obtained through in-person consultations with doctors. However, the COVID-19 pandemic has necessitated changes in interaction patterns between patients and medical personnel due to the implementation of health protocols and social restrictions. Traditional face-to-face consultations not only increase the risk of transmission but also extend patient waiting times at clinics. Interviews with several patients revealed that most still rely on in-person meetings to obtain health information, necessitating a more efficient and secure technology-based solution. This study aims to develop E-Consul, an Android-based health consultation application that facilitates interactive communication between patients and doctors. Through this application, patients can ask questions in text format and receive immediate responses through the system. The application also features health articles that enable doctors to share knowledge with the public, as well as a first aid guide to improve patient preparedness. The results showed that E-Consul accelerated access to health information, reduced the need for in-person visits, and increased patient satisfaction. A pilot study of 10 respondents found that 90% strongly agreed and 10% agreed that the application facilitated consultations and was useful for obtaining health information. No respondents disagreed. These findings confirm that E-Consul is feasible to implement as a practical solution to support the transformation of inclusive, effective, and relevant digital medical services in the post-pandemic era.